Flame-retardant color master batch and preparation process thereof
By combining the carrier resin and modified magnesium hydroxide, flame retardant color masterbatch with excellent flame retardant properties and mechanical properties was prepared, which solved the problem of poor flame retardant properties of color masterbatch in the prior art, and achieved simplicity and ease of use The flame retardant masterbatch preparation process is suitable for the high performance needs of modern plastic products.
Patent Information
- Application Number
- CN202411447625.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing color masterbatch has poor flame retardant performance in plastic products, which is difficult to meet the needs of modern society for flame retardant and anti-aging properties, and the preparation process is complex and costly.
The carrier resin, modified magnesium hydroxide, colorant and antioxidant were mixed and granulated by a twin screw extruder to prepare flame retardant masterbatch with excellent flame retardant properties and mechanical properties. Modified magnesium hydroxide forms an organic-inorganic flame retardant through chemical reactions of salicylic aldehyde, p-phenylenediamine and DOPO, and is coated on the surface of hexagonal sheet magnesium hydroxide to improve its dispersion and compatibility, and with the carrier The resin forms a hard and dense carbonized layer, enhancing flame retardant properties.
The prepared flame retardant masterbatch has excellent flame retardant properties, wear resistance and mechanical properties, stable and long-lasting, easy to obtain raw materials, simple processing process, large-scale promotion, flame retardant grade reaches V-0, and high oxygen index. , low smoke density and low wear value.
Smart Images

Figure BDA0005088143290000101 
Figure BDA0005088143290000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a flame retardant masterbatch and a preparation process thereof. Background Art
[0002] With the rapid development of modern society, plastic products are widely used in daily life and industrial production because of their lightness, durability, good plasticity and low cost. Masterbatch is one of the most important additives in the production process of plastic products, and people have higher and higher requirements for the performance of masterbatch. However, ordinary masterbatch in plastic products often only provides rich colors for products and improves the aesthetics of products. It has general wear resistance and weak impact resistance, which makes it difficult to meet the current demand for masterbatch in plastic products. The single performance of masterbatch directly affects the use field of plastic products.
[0003] As is known to all, plastic products are easy to burn in fire, and even melt droplets may appear, causing the fire to spread. When burning, toxic gases are released, so the masterbatch needs to have flame retardant ability to reduce the risk of fire spreading in plastic products. The Chinese patent application document with patent application number CN102070817A discloses a masterbatch for food packaging and a method for manufacturing the same. The masterbatch for food packaging has acid and alkali resistance, and includes the following components and their weight parts: 40-60 parts of low-density polyethylene, 40-45 parts of acid and alkali resistant pigments, 25-45 parts of organic pigments, 1-5 parts of zinc stearate, 16-20 parts of aluminum-titanium composite coupling agents, 1-5 parts of polyethylene wax and 0-10 parts of calcium carbonate. The masterbatch has good dispersibility and surface gloss, has certain acid and alkali resistance, and is not easy to fade. However, its application field is limited to thermoplastic plastic products, the preparation process is relatively complicated, and the product does not have flame retardancy and anti-aging properties. The Chinese patent application document with patent application number CN115592839A discloses a preparation process of an environmentally friendly masterbatch formula, including the following steps: S1, raw material preparation; S2, masterbatch production; S3, flame retardant layer coating; S4, antioxidant layer coating; S5, anti-agglomeration treatment; S6, storage environment. The invention relates to the preparation of flame retardant and environmentally friendly masterbatch, including first preparing a flame retardant solution, first mixing the flame retardant and half of the heat stabilizer and dispersant, adding them into a blender for stirring, taking them out, preparing a flame retardant solution, and then immersing the masterbatch carrier in the flame retardant solution, taking them out, and preparing a flame retardant and environmentally friendly masterbatch, wherein the flame retardant comprises a mixture of phosphate triester, magnesium hydroxide and hydroxyaluminum. The flame retardant components of the flame retardant and environmentally friendly masterbatch of the invention are simple, the flame retardant and smoke suppression effects are limited, and they need to be modified and protected through multiple links such as antioxidant layer coating and anti-agglomeration treatment, and the process is complicated and the cost is high.
[0004] Therefore, developing a masterbatch with excellent flame retardant properties is a technical problem that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to provide a flame retardant masterbatch and a preparation process thereof, so as to solve the problem that the masterbatch in the prior art has poor flame retardant performance.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] The first aspect of the present invention provides a flame retardant masterbatch, comprising the following raw materials in parts by weight:
[0008] Carrier resin: 65-90 parts;
[0009] Modified magnesium hydroxide: 25-45 parts;
[0010] Colorant: 15-45 parts;
[0011] Dispersant: 1-5 parts;
[0012] Antioxidant: 0.05-1 part.
[0013] In some possible implementations, the modified magnesium hydroxide is prepared by the following steps:
[0014] Hexagonal flaky magnesium hydroxide is added to anhydrous ethanol, stirred until uniformly dispersed, salicylaldehyde and p-phenylenediamine are added, refluxed at 80-85°C for 2-3h, and then DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) is added, stirring is continued for 10-12h, filtered, washed, and vacuum dried to obtain modified magnesium hydroxide. By using salicylaldehyde, p-phenylenediamine and DOPD to react chemically and then coating the surface of hexagonal flaky magnesium hydroxide, an organic-inorganic magnesium hydroxide flame retardant is obtained, which reduces the maximum surface energy of hexagonal flaky magnesium hydroxide, avoids stacking, agglomeration and the like, and improves the dispersibility and compatibility of magnesium hydroxide in the carrier resin.
[0015] In some possible implementations, the usage ratio of hexagonal flaky magnesium hydroxide, anhydrous ethanol, salicylaldehyde, p-phenylenediamine and DOPO is 1.0-1.5 g: 50 mL: 1.0-1.1 g: 0.40-0.42 g: 1.60-1.65 g.
[0016] In some possible implementations, the carrier resin is one of polyethylene resin, polycarbonate resin, and polypropylene resin.
[0017] In some possible implementations, the colorant includes at least one of cadmium red, cadmium yellow, cadmium orange, titanium white, carbon black, iron oxide red, cobalt blue, and cobalt green.
[0018] In some possible implementations, the dispersant is at least one of paraffin wax, ethylene bisstearamide (EBS), polyethylene wax, magnesium stearate, and calcium stearate.
[0019] In some possible implementations, the antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant.
[0020] The second aspect of the present invention provides a process for preparing a flame retardant masterbatch, comprising the following steps:
[0021] S1. Weigh the carrier resin, modified magnesium hydroxide, colorant, dispersant and antioxidant in parts by weight and add them into a high-speed mixer to mix them evenly to obtain a mixture;
[0022] S2. The mixed material is transferred to a twin-screw extruder, and flame retardant masterbatch is obtained after melt mixing, extrusion granulation and drying.
[0023] In some possible implementations, the rotation speed of the high-speed mixer in S1 is 160-200 r / min, and the mixing time is 1-2 h.
[0024] In some possible implementations, the screw speed of the twin-screw extruder in S2 is 250-300r / min, wherein the temperature of zone 1 is 140-160°C, the temperature of zone 2 is 160-180°C, the temperature of zone 3 is 190-210°C, the temperature of zone 4 is 180-220°C, the temperature of zone 5 is 190-210°C, and the die temperature is 160-180°C.
[0025] Beneficial effects of the present invention:
[0026] 1) The present invention provides a flame retardant masterbatch and a preparation process thereof, wherein a carrier resin, modified magnesium hydroxide, a colorant, a dispersant and an antioxidant are mixed, melt blended in a granulator, and extruded and granulated to obtain a flame retardant masterbatch. The flame retardant masterbatch prepared by the present invention has excellent flame retardant properties and mechanical properties, and is stable and durable; at the same time, the raw materials for preparing the flame retardant masterbatch are easily available, the processing process is simple, and large-scale promotion can be achieved.
[0027] 2) The modified magnesium hydroxide in the present invention undergoes a Schiff base reaction with salicylaldehyde, p-phenylenediamine and DOPD to form a compound containing phosphorus and nitrogen elements, and is coated on the surface of hexagonal flaky magnesium hydroxide through the interaction between the phenolic hydroxyl group of salicylaldehyde and the metal ions in the magnesium hydroxide, and finally forms an organic-inorganic combined flame retardant. At this time, the modified magnesium hydroxide interacts with the carrier resin as a flame retardant to form a hard and dense carbonized layer, which improves the flame retardant properties of the masterbatch and also plays a smoke suppression role. In addition, the DOPO structure can be combined with nitrogen-, sulfur- or boron-containing compounds, and the synergistic effect of the flame retardant groups is used to form an insulating multi-space sparse expansion carbon layer during combustion, which acts as a barrier to air, heat and pyrolysis products during thermal decomposition. Therefore, due to the double-layer barrier effect of the organic coke and the metal protective layer, the phosphorus-nitrogen synergistic effect and the free radical quenching effect, the prepared masterbatch has excellent thermal and flame retardant properties. At the same time, magnesium hydroxide with a lamellar structure, which has self-lubrication, anisotropy, good thermal conductivity and mechanical strength, is added as a filler to significantly improve the mechanical strength and wear resistance of the carrier resin.
[0028] 3) The masterbatch prepared by the present invention has a tensile strength of more than 36.5 MPa, an elongation at break of more than 226%, an oxygen index of more than 37%, a smoke density of less than 63%, a flame retardant grade of V-0, and an abrasion value of less than 0.15 g, and has the characteristics of excellent flame retardancy, good wear resistance, and excellent mechanical properties. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The hindered phenol antioxidant used in the examples and comparative examples of the present invention is antioxidant 1010, purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd.; the MgCl 2 , purchased from China Western Mining Group and purified by recrystallization before use; the salicylaldehyde used was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; the polyethylene resin used was purchased from Shanghai Dingfen Chemical Technology Co., Ltd.; the cadmium red used was purchased from Jinan Longsheng Dye Chemical Co., Ltd.; the other reagents without indicating the manufacturer can be purchased as conventional products on the market.
[0031] The hexagonal flaky magnesium hydroxide used in the present invention is prepared by the following steps:
[0032] 2 mL MgCl 2solution (1 mol / L) and 25 mL NH 3 ·H 2 O (10 mol / L), stirred for 10 min, added 3 mL of sodium dodecyl sulfate, continued stirring for 30 min and then transferred to a tetrafluoroethylene-lined autoclave, sealed and subjected to hydrothermal reaction at 120 ° C for 12 h. After the autoclave was cooled to room temperature, the white precipitate was collected, washed with distilled deionized water and anhydrous ethanol for 3 times respectively, and dried in a vacuum drying oven at 80 ° C for 6 h to obtain hexagonal flaky magnesium hydroxide.
[0033] Example 1
[0034] This embodiment provides a modified magnesium hydroxide, and the preparation steps are as follows:
[0035] 1.0 g of hexagonal flaky magnesium hydroxide was added to 50 mL of anhydrous ethanol, stirred until uniformly dispersed, 1.0 g of salicylaldehyde and 0.40 g of p-phenylenediamine were added, and the mixture was refluxed at 80° C. for 3 h. Subsequently, 1.60 g of DOPO was added, and stirring was continued for 10 h. The mixture was filtered, washed with anhydrous ethanol and deionized water for 3 times respectively, and dried in a vacuum drying oven at 60° C. for 12 h to obtain modified magnesium hydroxide.
[0036] Example 2
[0037] This embodiment provides a modified magnesium hydroxide, and the preparation steps are as follows:
[0038] 1.45 g of hexagonal flaky magnesium hydroxide was added to 50 mL of anhydrous ethanol, stirred until uniformly dispersed, 1.1 g of salicylaldehyde and 0.41 g of p-phenylenediamine were added, and the mixture was refluxed at 80° C. for 3 h. Subsequently, 1.65 g of DOPO was added, and stirring was continued for 10 h. The mixture was filtered, washed with anhydrous ethanol and deionized water for 3 times respectively, and dried in a vacuum drying oven at 60° C. for 12 h to obtain modified magnesium hydroxide.
[0039] Comparative Example 1
[0040] This comparative example provides a modified magnesium hydroxide, and the preparation steps are as follows:
[0041] Add 1.0 g of hexagonal flaky magnesium hydroxide to 50 mL of anhydrous ethanol, stir until evenly dispersed, add 1.0 g of salicylaldehyde and 0.40 g of p-phenylenediamine, reflux at 80 ° C for 3 h, continue stirring for 10 h, filter, wash with anhydrous ethanol and deionized water for 3 times respectively, place in a 60 ° C vacuum drying oven for 12 h to obtain modified magnesium hydroxide.
[0042] Comparative Example 2
[0043] This comparative example provides a modified magnesium hydroxide, and the preparation steps are as follows:
[0044] The modified magnesium hydroxide is the hexagonal flaky magnesium hydroxide prepared by the present invention.
[0045] Example 3
[0046] This embodiment provides a flame retardant masterbatch, comprising the following raw materials in parts by weight:
[0047] Polyethylene resin: 65 parts, modified magnesium hydroxide in Example 1: 25 parts, cadmium red: 15 parts, paraffin: 2 parts, antioxidant 1010: 0.05 parts.
[0048] The preparation steps of the flame retardant masterbatch are as follows:
[0049] S1. Weigh the polyethylene resin, the modified magnesium hydroxide, cadmium red, paraffin and antioxidant 1010 in Example 1 in parts by weight and add them into a high-speed mixer to mix them evenly. The speed of the high-speed mixer is 160 r / min and the mixing time is 2 h to obtain a mixture.
[0050] S2. The mixed material is transferred to a twin-screw extruder for melt mixing, wherein the screw speed of the twin-screw extruder is 250 r / min, wherein the temperature of zone 1 is 140°C, the temperature of zone 2 is 160°C, the temperature of zone 3 is 190°C, the temperature of zone 4 is 180°C, the temperature of zone 5 is 190°C, the temperature of the die head is 160°C, and the flame retardant masterbatch is obtained after extrusion granulation and drying.
[0051] Example 4
[0052] Compared with Example 3, the only difference is:
[0053] 25 parts of the modified magnesium hydroxide in Example 1 were replaced with 25 parts of the modified magnesium hydroxide in Example 2.
[0054] Example 5
[0055] Compared with Example 3, the only difference is:
[0056] 25 parts of the modified magnesium hydroxide in Example 1 were replaced by 35 parts of the modified magnesium hydroxide in Example 1.
[0057] Example 6
[0058] Compared with Example 3, the only difference is:
[0059] 25 parts of the modified magnesium hydroxide in Example 1 were replaced by 45 parts of the modified magnesium hydroxide in Example 1.
[0060] Example 7
[0061] Compared with Example 3, the only difference is:
[0062] Polyethylene resin: 75 parts, modified magnesium hydroxide in Example 1: 30 parts, cadmium red: 25 parts, paraffin: 3 parts, antioxidant 1010: 0.15 parts.
[0063] Example 8
[0064] Compared with Example 3, the only difference is:
[0065] Polyethylene resin: 88 parts, modified magnesium hydroxide in Example 1: 42 parts, cadmium red: 40 parts, paraffin: 4 parts, antioxidant 1010: 0.85 parts.
[0066] Example 9
[0067] Compared with Example 3, the only difference is:
[0068] The preparation steps of the flame retardant masterbatch are as follows:
[0069] S1. Weigh the polyethylene resin, the modified magnesium hydroxide, cadmium red, paraffin and antioxidant 1010 in Example 1 in parts by weight and add them into a high-speed mixer to mix them evenly. The speed of the high-speed mixer is 190 r / min and the mixing time is 1.5 h to obtain a mixture.
[0070] S2. The mixed material is transferred to a twin-screw extruder for melt mixing, wherein the screw speed of the twin-screw extruder is 250 r / min, wherein the temperature of zone 1 is 140°C, the temperature of zone 2 is 160°C, the temperature of zone 3 is 190°C, the temperature of zone 4 is 180°C, the temperature of zone 5 is 190°C, the temperature of the die head is 160°C, and the flame retardant masterbatch is obtained after extrusion granulation and drying.
[0071] Example 10
[0072] Compared with Example 3, the only difference is:
[0073] The preparation steps of the flame retardant masterbatch are as follows:
[0074] S1. Weigh the polyethylene resin, the modified magnesium hydroxide, cadmium red, paraffin and antioxidant 1010 in Example 1 in parts by weight and add them into a high-speed mixer to mix them evenly. The speed of the high-speed mixer is 160 r / min and the mixing time is 2 h to obtain a mixture.
[0075] S2. The mixed material is transferred to a twin-screw extruder and melt-mixed. The screw speed of the twin-screw extruder is 280 r / min. The temperature of zone 1 is 155°C, the temperature of zone 2 is 170°C, the temperature of zone 3 is 200°C, the temperature of zone 4 is 210°C, the temperature of zone 5 is 210°C, and the temperature of the die head is 180°C. After extrusion granulation and drying, flame retardant masterbatch is obtained.
[0076] Comparative Example 3
[0077] Compared with Example 3, the only difference is:
[0078] 25 parts of the modified magnesium hydroxide in Example 1 were replaced by 25 parts of the modified magnesium hydroxide in Comparative Example 1.
[0079] Comparative Example 4
[0080] Compared with Example 3, the only difference is:
[0081] 25 parts of the modified magnesium hydroxide in Example 1 were replaced by 25 parts of the modified magnesium hydroxide in Comparative Example 2.
[0082] Comparative Example 5
[0083] Compared with Example 3, the only difference is:
[0084] 25 parts of the modified magnesium hydroxide in Example 1 were replaced by 20 parts of the modified magnesium hydroxide in Example 1.
[0085] Comparative Example 6
[0086] Compared with Example 3, the only difference is:
[0087] 25 parts of the modified magnesium hydroxide in Example 1 were replaced with 55 parts of the modified magnesium hydroxide in Example 1.
[0088] Comparative Example 7
[0089] Compared with Example 3, the only difference is:
[0090] Polyethylene resin: 55 parts, modified magnesium hydroxide in Example 1: 25 parts, cadmium red: 15 parts, paraffin: 2 parts, antioxidant 1010: 0.05 parts.
[0091] Comparative Example 8
[0092] Compared with Example 3, the only difference is:
[0093] Polyethylene resin: 55 parts, modified magnesium hydroxide in Example 1: 20 parts, cadmium red: 15 parts, paraffin: 1 part, antioxidant 1010: 0.05 parts.
[0094] Comparative Example 9
[0095] Compared with Example 3, the only difference is:
[0096] The preparation steps of the flame retardant masterbatch are as follows:
[0097] S1. Weigh the polyethylene resin, the modified magnesium hydroxide in Example 1, cadmium red, paraffin and antioxidant 1010 in parts by weight and add them into a high-speed mixer for uniform mixing. The speed of the high-speed mixer is 140 r / min and the mixing time is 2 h to obtain a mixture.
[0098] Comparative Example 10
[0099] Compared with Example 3, the only difference is:
[0100] The preparation steps of the flame retardant masterbatch are as follows:
[0101] S2. The mixed material is transferred to a twin-screw extruder and melt-mixed. The screw speed of the twin-screw extruder is 250 r / min. The temperature of zone 1 is 130°C, the temperature of zone 2 is 150°C, the temperature of zone 3 is 175°C, the temperature of zone 4 is 170°C, the temperature of zone 5 is 220°C, the temperature of the die head is 160°C, and the flame-retardant masterbatch is obtained after extrusion granulation and drying.
[0102] The masterbatches obtained in Examples 3 to 10 and Comparative Examples 3 to 10 were tested for performance:
[0103] 1) Tensile strength and elongation at break test: The tensile properties of the cable material are tested according to GB / T1040.3-2006 standard;
[0104] 2) Oxygen index test: According to GB / T 2406.3-2022 standard test, the cable material is subjected to high temperature test to determine its oxygen index;
[0105] 3) Smoke density test: According to GB / T8323.2-2008 standard test, the smoke density test method of the single chamber method is used to test the smoke density of the electrical material;
[0106] 4) Flame retardant performance test: The flame retardant performance test is carried out in accordance with the vertical burning test specified in GB / T 2408-2021.
[0107] 5) Wear resistance test: Use Taber abrasion tester to test the wear resistance of the sample. Place two grinding wheels on the sample and set the grinding wheel moving speed to 30r / min to perform wear test on the sample. Record the initial mass of the sample and the mass of the sample after 2000 revolutions of wear. The formula for calculating the sample wear value is as follows:
[0108] Q = Mm;
[0109] Where Q is the wear value of the sample, g / 2000r; M is the initial mass of the sample, g; m is the mass of the sample after grinding, g.
[0110] The results are shown in Table 1:
[0111] Table 1
[0112]
[0113]
[0114] It can be seen from Table 1 that the mechanical properties and flame retardant properties of the masterbatches prepared in Examples 3-10 are higher than those in Comparative Examples 3-10. It can be seen that the masterbatches provided by the present invention have excellent flame retardant properties, wear resistance and mechanical properties.
[0115] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0116] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A flame retardant masterbatch, characterized in that: It includes the following raw materials in parts by weight: Carrier resin: 65-90 parts; Modified magnesium hydroxide: 25-45 parts; Colorant: 15-45 parts; Dispersant: 1-5 parts; Antioxidant: 0.05-1 part.
2. A flame retardant masterbatch according to claim 1, characterized in that: The modified magnesium hydroxide is prepared by the following steps: Add hexagonal flaky magnesium hydroxide to anhydrous ethanol, stir until evenly dispersed, add salicylaldehyde and p-phenylenediamine, reflux at 80-85° C. for 2-3 hours, then add DOPO, continue stirring for 10-12 hours, filter, wash, and vacuum dry to obtain modified magnesium hydroxide.
3. A flame retardant masterbatch according to claim 2, characterized in that: The dosage ratio of hexagonal flaky magnesium hydroxide, anhydrous ethanol, salicylaldehyde, p-phenylenediamine and DOPO is 1.0-1.5 g: 50 mL: 1.0-1.1 g: 0.40-0.42 g: 1.60-1.65 g.
4. The flame retardant masterbatch according to claim 1, characterized in that: The carrier resin is one of polyethylene resin, polycarbonate resin and polypropylene resin.
5. The flame retardant masterbatch according to claim 1, characterized in that: The colorant includes at least one of cadmium red, cadmium yellow, cadmium orange, titanium white, carbon black, iron oxide red, cobalt blue and cobalt green.
6. The flame retardant masterbatch according to claim 1, characterized in that: The dispersant is at least one of paraffin wax, vinyl bisstearamide, polyethylene wax, magnesium stearate and calcium stearate.
7. The flame retardant masterbatch according to claim 1, characterized in that: The antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant.
8. The process for preparing a flame retardant masterbatch according to claim 1, characterized in that: The following steps are involved: S1. Weigh the carrier resin, modified magnesium hydroxide, colorant, dispersant and antioxidant in parts by weight and add them into a high-speed mixer to mix them evenly to obtain a mixture; S2. The mixed material is transferred to a twin-screw extruder, and flame retardant masterbatch is obtained after melt mixing, extrusion granulation and drying.
9. The process for preparing a flame retardant masterbatch according to claim 8, characterized in that: The speed of the high-speed mixer in S1 is 160-200r / min, and the mixing time is 1-2h.
10. The process for preparing a flame retardant masterbatch according to claim 8, characterized in that: The screw speed of the twin-screw extruder in S2 is 250-300r / min, wherein the temperature of zone 1 is 140-160°C, the temperature of zone 2 is 160-180°C, the temperature of zone 3 is 190-210°C, the temperature of zone 4 is 180-220°C, the temperature of zone 5 is 190-210°C, and the die head temperature is 160-180°C.
Citation Information
Patent Citations
Modified flame-retardant color master batch and preparation method thereof
CN113462058A
Phosphorus-nitrogen synergistic flame retardant compound as well as preparation method and application thereof
CN114031642A
Cited By
Flame-retardant antioxidant color master batch and preparation method thereof
CN119978458A